2016
DOI: 10.18504/pl2448-009-2016
|View full text |Cite
|
Sign up to set email alerts
|

Fronteras simbólicas y clases medias. Movilidad social en Chile

Abstract: ResumenA más de tres décadas de la aplicación de las políticas de ajuste estructural en Chile, las clases medias han aumentado su peso en la estructura social y han cambiado su sector económico, empleo y trayectorias de movilidad social. Este artículo analiza la percepción de las fronteras simbólicas que, emergentes de estos procesos macrosociales, van moldeando las subjetividades de los sujetos pertenecientes a las clases medias en procesos de movilidad social ascendente y se relacionan con las percepciones s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
2
9
0
10
Order By: Relevance
“…However, those who actually experienced residential mobility tended to maintain deep emotional affinities to their stigmatized neighborhoods, something consistent with similar results in international research (Jorgensen, 2010; Kirkness, 2014; Manzo et al, 2008; Ortega, 2014). These results are aligned with some studies focused on the subjective implications of social mobility, as people may feel as an outsider in the new place, and indebted with the place of origin, feeling that they have to give back to the childhood neighborhood (e.g., Castillo, 2016; De Gaulejac, 2008; Salinas & Riquelme, 2015; Walkerdine, 2003):
Maybe I will work for the wealthy, to win more money, but I will also work in deprived neighbourhoods. And I will work there without any payment, because there you find people who really needs it.
…”
Section: Social Exclusion Place and Stigmasupporting
confidence: 88%
See 1 more Smart Citation
“…However, those who actually experienced residential mobility tended to maintain deep emotional affinities to their stigmatized neighborhoods, something consistent with similar results in international research (Jorgensen, 2010; Kirkness, 2014; Manzo et al, 2008; Ortega, 2014). These results are aligned with some studies focused on the subjective implications of social mobility, as people may feel as an outsider in the new place, and indebted with the place of origin, feeling that they have to give back to the childhood neighborhood (e.g., Castillo, 2016; De Gaulejac, 2008; Salinas & Riquelme, 2015; Walkerdine, 2003):
Maybe I will work for the wealthy, to win more money, but I will also work in deprived neighbourhoods. And I will work there without any payment, because there you find people who really needs it.
…”
Section: Social Exclusion Place and Stigmasupporting
confidence: 88%
“…Research on social mobility and its links to subjectivity and identity, however, has shown that these processes are not unproblematic. Specifically, research on people's upward social mobility trajectories indicate that the process implies affective and identity contradictions, which resonate around a tension between “who I am” and “who I want to be” (Castillo, 2016; Salinas & Riquelme, 2015; Walkerdine, 2003). Stephanie Taylor (2005), for example, addresses residential mobility as a challenging process that questions individuals' place identity, foregrounding contradictions in the narrative accounts of self‐identity (i.e., “identity trouble”) through which they make sense of their lives as emplaced subjects.…”
Section: Social Exclusion Place and Stigmamentioning
confidence: 99%
“…Asimismo, diferentes estudios (Chavez y Flores, 2017;Duk y Murillo, 2019;Silva-Peña, 2020;Valenzuela, Bellei y De Los Ríos, 2014) han sido categóricos a la hora de indicar que el sistema educativo chileno tiene severos problemas de segregación (en términos socioeconómicos, culturales, étnicos, etc.). De hecho, además de ofrecer casi nulas posibilidades de movilidad social (Castillo, 2016), no otorga a los sectores con menores ingresos de la población la posibilidad de acceder a centros educativos con estándares elevados de calidad (Barahona, Veres y Barahona, 2018).…”
Section: Revisión De La Literaturaunclassified
“…Carmen gives voice to the way many respondents see their upward trajectories: as a continual process involving great and sustained effort and sacrifices to reach their current position of improved occupational and economic conditions. Moreover, as Blanca suggests, this invocation of effort is often closely tied to a clear differentiation from people from privileged backgrounds with whom they have interacted at university or in occupational settings -an element which is central for their boundary-making undertaken by the upwardly mobile (Castillo, 2016;UNDP, 2017: 247-248). Carmen's interpretation of effort is confirmed by Cristina Martínez, an electrical engineer from UCH, who makes an explicit contrast between privileged people, and those like herself who come from disadvantaged backgrounds: 'My story makes me value things.…”
Section: Belonging To 'People Of Effort'mentioning
confidence: 99%